Growth performance and metabolic responses to dietary protein/carbohydrate ratios in pacu (Piaractus mesopotamicus) juveniles - Pereira, Mayara de Moura [UNESP]; Nagata, Mariana Midori [UNESP]; Enes, Paula; Oliva-Teles, Aires; Urbinati, Elisabeth Criscuolo [UNESP]; Takahashi, Leonardo Susumu [UNESP] (Hindawi, 2020)
Proper inclusion of carbohydrates in aquafeeds can increase protein and lipid retention preventing the catabolism of these nutrients for energy purposes. This research aimed to evaluate performance, metabolic and enzymatic indicators in pacu (Piaractus mesopotamicus) juveniles fed diets with 350 or 400 g/kg starch (S) and 190 or 210 g/kg digestible protein (P) (diets S35P19, S35P21, S40P19 and S40P21 respectively). Overall, the best growth performance was achieved with diet S35P21. Dietary protein and starch levels had no effect on feed intake, feed conversion ratio and protein efficiency ratio. The lowest whole-body protein content was recorded in fish fed the S35P19 diet, while fish fed diet S40P21 presented the highest whole-body lipid content. Regardless of dietary protein level, S40 diets led to higher plasma glucose and triglycerides levels, and higher liver glycogen content. No differences were observed on hepatosomatic index or muscle lipids content. Increasing dietary starch level led to an increase in mesenteric fat index and in liver glucokinase activity, while higher dietary protein promoted a decrease in liver lipid content. Fish fed diet S40P21 showed higher liver glucose-6-phosphate dehydrogenase activity than fish fed the S35P21 and S40P19 diets. Dietary protein and starch levels had no effect on pyruvate kinase and fructose-1,6-bisphosphatase activity. Overall, dietary starch enhanced glycolytic and lipogenic pathways but did not depress gluconeogenic pathway. The results of this study indicate that a diet with 350 g/kg starch and 210 g/kg digestible protein was the most adequate for pacu in terms of growth performance and feed utilization.
Keywords: glycolysis; intermediary metabolism; lipogenesis; nutrition; starch